2019
DOI: 10.3389/fimmu.2019.02798
|View full text |Cite
|
Sign up to set email alerts
|

A Biodegradable Mg-Based Alloy Inhibited the Inflammatory Response of THP-1 Cell-Derived Macrophages Through the TRPM7–PI3K–AKT1 Signaling Axis

Abstract: Mg-based alloys might be ideal biomaterials in clinical applications owing to favorable mechanical properties, biodegradability, biocompatibility, and especially their anti-inflammatory properties. However, the precise signaling mechanism underlying the inhibition of inflammation by Mg-based alloys has not been elucidated. Here, we investigated the effects of a Mg-2.1Nd-0.2Zn-0.5Zr alloy (denoted as JDBM) on lipopolysaccharide (LPS)-induced macrophages. THP-1 cell-derived macrophages were cultured on JDBM, Ti−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…TRPM7 kinase-deficient murine neutrophils also displayed reduced chemotaxis toward a CXCL1 gradient, which was further decreased upon TRPM7 channel blockade using NS8593, suggesting that TRPM7 channel function, at least in part, acts independent of TRPM7 kinase due to ion conductance. Previously, TRPM7 activity has already been implicated alongside PI3 kinase signaling pathways ( 10 , 45 , 46 ), however, as of now the impact of TRPM7 channel versus kinase moiety on different PI3K isoforms remains to be established. We here used PI3K isoform specific inhibitors as well as genetic inactivation of TRPM7 kinase to shed light on their interrelationship.…”
Section: Discussionmentioning
confidence: 99%
“…TRPM7 kinase-deficient murine neutrophils also displayed reduced chemotaxis toward a CXCL1 gradient, which was further decreased upon TRPM7 channel blockade using NS8593, suggesting that TRPM7 channel function, at least in part, acts independent of TRPM7 kinase due to ion conductance. Previously, TRPM7 activity has already been implicated alongside PI3 kinase signaling pathways ( 10 , 45 , 46 ), however, as of now the impact of TRPM7 channel versus kinase moiety on different PI3K isoforms remains to be established. We here used PI3K isoform specific inhibitors as well as genetic inactivation of TRPM7 kinase to shed light on their interrelationship.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the influence of the bare and PCL-based coated AZ31 Mg alloy on the immune response, the cellular model was represented by the monocyte/macrophage cell line RAW 264.7. In the specialised literature, studies reported the use of the human monocytic cell line THP-1 [ 99 , 100 , 101 , 102 , 103 ]. However, the mouse RAW 264.7 cell line, regardless of its transformed phenotype, is generally used in inflammation studies due to its response to Escherichia coli LPS which can imitate bacterial stimuli [ 98 , 104 , 105 , 106 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies reported that Mg from the degradation products of JDBM inhibited the inflammatory response of THP-1 cellderived macrophages through the TRPM7-PI3K-AKT1 signaling axis. Furthermore, Mg ions scavenged intracellular reactive oxygen species (ROS) to prevent the inflammatory response based on the LPS-induced activation of the TLR-4-MYD88-NF-κB/MAPK signaling pathway (29). However, up to now, studies on the regulation of macrophage polarization by Mg ions are still limited.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the Mg-Nd-Zn-Zr alloy ingot (denoted as JDBM), which was especially designed for vascular stents, has been described in previous studies. The composition of the biodegradable JDBM alloy is as follows (mass percent): Mg: >97%, Nd: 2.1%, Zn: 0.21%, Zr: 0.5%, Mn: 0.009%, Si: 0.006%, Cu: 0.005%, Fe: 0.002% (29)(30)(31)(32). JDBM discs (18 mm in diameter and 2.0 mm in height) were immersed in an ultrasonic cleaning bath with ethanol and acetone for 10 min and then sterilized by exposure to ultraviolet light for 1 h before use.…”
Section: Jdbm Extract Preparationmentioning
confidence: 99%